Evaluation of management strategies in Ningaloo Marine Park, Western Australia. (1st January 2014) - Thébaud, Olivier; Little, L. Richard; Fulton, Elizabeth
The spatial, multi-species nature of coral reef fisheries makes them notoriously difficult to manage. We have developed a simulation modelling approach to examine the effect of management options on the recreational fishery of Ningaloo Reef in Western Australia, that targets Spangled Emperor ( Lethrinus nebulosus ) model. Results show the effects of historical fishing mortality on the depletion of Spangled Emperor and the potential biological and social effects of changes in the sanctuary zones under a range of scenarios. The inherent trade-offs between the ecological and social objectives identified by the stakeholders are characterised. Some management strategies clearly perform better than others with respect to the social objectives pursued in the fishery, although none manages to improve its ecological status.